Together they can complete the whole job in 6 minutes.
The amount of work done by the slowest person is .
The time, work and rate formula is given by
Work done = time × rate of wok
According to the given question.
One person can do a certain job is 10 minutes.
⇒ The work done in 1 minute by the first person or the rate of work done by the first person =
Another person can do the same job in 15 minutes.
⇒ The work done in 15 minutes by another person or the rate of work done by the second person =
So,
The amount of work done by both of them in one minute
=
⇒ Together they can complete the th part of the work in one minute.
Therefore, together they can complete the whole job in 6 minutes.
As, we know that
Work done = Total time taken × Rate of work done
Since, the second person is taking 15 minutes to complete the jo.
So, he is the slowest person.
Total time total time taken by the two persons to complete the job together is x (given).
Also, the rate of work done by the slowest person =
Therefore,
The amount of work done by the slowest person =
Hence, the amount of work done by the slowest person is .
Find out more information about the work rate here:
#SPJ3
3x-y=7
Answer:
b
Step-by-step explanation:
Answer:
30*x + 14850/x
Step-by-step explanation:
Let x be the length of the two opposite sides of the region with material costs of $15 per linear foot.
Let y be the length of the other two sides
Now, we have the following equations
Area of the rectangular región = x * y = 450 ft2
Total cost of fencing = 15*x + 15*x + 15 *y + 18*y
Total cost of fencing = 30*x + 33 *y
We now that area is equal to 450 ft2 = x*y
So y = 450/x
Now we can substitute y in equation for Total cost of fencing and obtain a function that expresses the cost of fencing the region in terms of the length, x
Total cost of fencing = 30*x + 33 *(450/x)
Total cost of fencing = 30*x + 14850/x
2y – 4x =
Answer:
-10
Step-by-step explanation:
Answer:
Step-by-step explanation:
El método de reducción también llamado Suma y Resta, consiste en multiplicar una o ambas ecuaciones de tal manera que los coeficientes de una de las incógnitas sean iguales y de signo contrario, de tal forma que se eliminen al sumar las ecuaciones.
Nuestras ecuaciones son:
En este caso podemos observar que x y -x son iguales y de signo contrario así que no tendremos que multiplicar y podemos sumar ambas ecuaciones.
Al sumarlas tenemos que:
Ahora sustituímos el valor que encontramos de y en la segunda ecuación para poder obtener el valor de x.
Por lo tanto, x = 0 y y = 2